Complete heart block in lupus. (November 2019) - Natsheh, A; Shimony, D; Bogot, N; Nesher, G; Breuer, G S
Conduction abnormalities are uncommon in adult patients with lupus. We present a young woman with recurrent syncope caused by third-degree atrio-ventricular block as the initial manifestation of lupus and review 31 additional cases of systemic lupus erythematosus patients that have been described previously with complete heart block. Heart blocks occurred almost exclusively in females. The median age was 37 years. In 24 cases heart blocks were diagnosed in patients with established lupus. In only five patients, including the patient presented here, heart blocks were diagnosed before the lupus diagnosis. Syncope was the most common presenting symptom of heart block. Electrocardiographic findings prior to heart block episodes were reported in 17 cases: eight had normal findings, but nine had already variant forms of atrioventricular or intraventricular conduction defects. Anti-nuclear antibody tests were reported in 25 cases and were all positive. Anti-DNA antibodies were also common and were positive in 16 of 19 cases (84%). Anti-La and anti-Ro antibodies were less common (13% and 35%, respectively). Three patients died, all prior to 1975. Heart block resolved in 10 cases. Follow-up was reported in four of these cases and heart block recurred in three of them. A permanent pacemaker was the eventual treatment in 22 cases. The etiology of lupus-associated complete heart block is not clear. It is probably variable, possibly related to effects of autoantibodies reacting with the conduction system, myocardial disease and adverse effects of antimalarials. Insertion of a permanent pacemaker seems to be the preferable method of treatment.